2021
DOI: 10.2196/28864
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Sexual and Gender Minority Youth in HIV Interventions Through Gay Dating Apps: Recruitment Protocol

Abstract: Background HIV continues to disproportionately impact sexual and gender minority youth (SGMY) in the United States. Public health efforts have increasingly focused on developing efficacious interventions to curb the spread of HIV among SGMY and help those living with HIV achieve and sustain viral suppression. However, recruiting and engaging SGMY in prevention and care interventions is challenging. Objective During the past decade, gay dating apps have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although Facebook has historically been a site that has significantly improved the engagement, screening, and enrollment of young sexual and gender minority adolescents [ 42 , 43 ], which overlaps with the population of youth living with HIV, we did not find paid screeners on Facebook to statistically significant increase participant enrollment. Although social media has also been successfully used to recruit participants either through advertisements [ 11 ] or direct recruitment [ 44 ], it is possible that the COVID-19 pandemic altered the way in which youth living with HIV used social media platforms, rendering them less effective for recruiting and enrolling eligible participants, despite the increased number of screeners.…”
Section: Discussionmentioning
confidence: 99%
“…Although Facebook has historically been a site that has significantly improved the engagement, screening, and enrollment of young sexual and gender minority adolescents [ 42 , 43 ], which overlaps with the population of youth living with HIV, we did not find paid screeners on Facebook to statistically significant increase participant enrollment. Although social media has also been successfully used to recruit participants either through advertisements [ 11 ] or direct recruitment [ 44 ], it is possible that the COVID-19 pandemic altered the way in which youth living with HIV used social media platforms, rendering them less effective for recruiting and enrolling eligible participants, despite the increased number of screeners.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that multiple exposures to ads via different outlets is a key element for effective health communication campaigns [ 39 ]. With more resources and time, we could have maximized reach by targeting other social media apps, as well as popular gay dating apps that have successfully engaged youth in HIV prevention research [ 23 , 40 ]. Lastly, we would have worked with the Louisiana Department of Health to design a TelePrEP website tailored to youth that would increase engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Teams in Los Angeles, CA, and New Orleans, LA, screened youth at risk for or living with HIV from agencies and adolescent medicine clinics. Recruitment was also done via social media dating apps 12 and referrals. Youth were eligible for enrollment either as (1) youth living with HIV (ATN 147 and 148 for recent and established infection, respectively) or (2) youth not living with HIV who had multiple risk factors for HIV: recent STIs, condomless sex, or substance use; lifetime experience of homelessness, mental health hospitalization, or criminal justice contact; SGM; Black or Latinx; reporting sex partners living with HIV; or current preexposure prophylaxis use (ATN 149).…”
Section: Methodsmentioning
confidence: 99%